What Future for the EU After Brexit? - Paul De Grauwe (Intereconomics, 2016)
How should the European Union react to the decision of the UK to withdraw from the union? This is the question that has been at the centre of the political debate in Europe since Brexit became a reality. In this article, I will first discuss the nature of the reforms that are called for as a result of the Brexit vote. I will then turn to the issue of the negotiating strategy that the EU should adopt towards the UK.
Keywords: 330